INTRACRANIAL HYPERTENSION: A RARE BUT IMPORTANT CAUSE OF HEADACHE IN A YOUNG FEMALE WITH CUSHING’S DISEASE - Jalal, Fadzliana Hanum; Rajoo, Subashini (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION Intracranial hypertension during the course of diagnosis and treatment in Cushing’s disease is rare. However, it carries significant morbidity. Headache and visual disturbance in patients with Cushing’s disease should alarm the physician of the diagnosis. Treatment options include carbonic anhydrase, loop diuretics and serial lumbar puncture as temporary measures for alleviating symptoms and preserve vision. RESULTS A 21-year-old female presented with symptoms of weight gain, intermittent headache, blurring of vision, and bilateral leg swelling. Her blood pressure was 140/88 mmHg, BMI was 34.5 kg/m2 . She had abdominal striae. There was no proximal myopathy. Visual confrontation and acuity were normal. Diagnosis of Cushing’s disease was confirmed with unsuppressed cortisol [426 nmol/L] post low-dose dexamethasone suppression test and elevated serum ACTH [14.7 pmol/L]. Pituitary MRI showed a 0.7 x 0.9 x 0.6 cm left pituitary microadenoma without evidence of optic chiasm compression or hydrocephalus. Baseline visual acuity and Humphrey visual field assessment were normal. At three months after initiation of oral ketoconazole 200 mg twice daily, she complained of worsening headache and blurring of vision. Funduscopy showed bilateral papilledema. Bjerrum’s chart examination showed bilateral enlargement of physiologic blind spots. Repeat pituitary MRI did not show any new significant findings. Lumbar puncture demonstrated marked increase in the opening pressure above 50 cmH20. Examination of the cerebrospinal fluid was normal. Oral acetazolamide 500 mg twice daily was commenced, however, this was complicated by hypotension and metabolic acidosis. Ketoconazole was re-introduced with careful titration and symptoms of worsening headache and vision were no longer observed. The patient subsequently underwent trans-sphenoidal surgery and is currently in remission. CONCLUSION Symptoms of headache and visual disturbance should prompt the physician to exclude intracranial hypertension in patients with Cushing’s disease in order to institute correct treatment and preserve vision